Characterization of Mutational Clusters in the N-Terminal Domain of SARS-CoV-2 Spike Protein - Saber, Noor; Kandala, Nuha J (Iraqi Journal of Science, 2026)
Since the first report of SARS-CoV-2 in Wuhan, China, the virus has undergone multiple mutations leading to the emergence of variants of concern. While mutations in the receptor binding domain (RBD) of the spike gene have been extensively studied, mutations and indels in the N-terminal domain (NTD) have received less attention. In this study, we use a simple and cost-effective Sanger sequencing approach by targeting a 757bp region in the NTD of the spike gene. Analysis results showed the dominancy of G142D mutation resulted from single nucleotide polymorphism (SNP). Furthermore, our results showed the prevalence of two distinctive mutational clusters, the first pattern includes the 69H/70V, 143V, 144Y, L212I, and 211N deletions, insertion of 214EPE and T95I substitution. The second cluster includes one amino acid change of V213G. Subsequent analysis revealed the persistence of these genetic changes in current global circulating strains and emergence of new low circulating mutations within studied viral isolates represented by W258G. Our findings highlight the genetic changes shared among the studied isolates, providing a mutational catalogue of the NTD region and establishing a reference database for further local studies. Additionally, this study introduces a novel primer pair, designed to enable a rapid and cost-effective approach for SARS-CoV-2 lineages tracking.